Computational study of molecular electrostatic potential, docking and dynamics simulations of gallic acid derivatives as ABL inhibitors. (June 2018) - Raghi, K.R.; Sherin, D.R.; Saumya, M.J.; Arun, P.S.; Sobha, V.N.; Manojkumar, T.K.
Graphical abstract: Highlights: Docking. Molecular Electrostatic Potential map. Molecular Dynamics. ABL Kinase Inhibitor. New Drug for CML. Abstract: Chronic myeloid leukemia (CML), a hematological malignancy arises due to the spontaneous fusion of the BCR and ABL gene, resulting in a constitutively active tyrosine kinase (BCR-ABL). Pharmacological activity of Gallic acid and 1, 3, 4-Oxadiazole as potential inhibitors of ABL kinase has already been reported. Objective of this study is to evaluate the ABL kinase inhibitory activity of derivatives of Gallic acid fused with 1, 3, 4-Oxadiazole moieties. Attempts have been made to identify the key structural features responsible for drug likeness of the Gallic acid and the 1, 3, 4-Oxadiazole ring using molecular electrostatic potential maps (MESP). To investigate the inhibitory activity of Gallic acid derivatives towards the ABL receptor, we have applied molecular docking and molecular dynamics (MD) simulation approaches. A comparative study was performed using Bosutinib as the standard which is an approved CML drug acting on the same receptor. Furthermore, the novel compounds designed and reported here in were evaluated for ADME properties and the results indicate that they show acceptable pharmacokinetic properties. Accordingly these compounds are predicted to be drug like with low toxicity potential.